PERFIL DAS DEMANDAS JUDICIAIS PARA FORNECIMENTO DE FÓRMULAS NUTRICIONAIS ENCAMINHADAS AO MINISTÉRIO DA SAÚDE DO BRASIL - Tatiane Nunes Pereira; Kimielle Cristina Silva; Ana Carolina Lucena Pires; Kelly Poliany de Souza Alves; Ana Silvia Pavani Lemos; Patricia Constante Jaime (Universidade do Estado do Rio de Janeiro, 2014)
Introduction: Health-related lawsuits against public agencies - including  requests for industrialized food formulas - have increased exponentially in Brazil over the last few years. They pose a significant challenge to managers of Brazil's Unified Health System (SUS). As health and feeding are rights under the Federal Constitution, filing of lawsuits has become a challenge to be faced by the Government. Objective: To describe lawsuits over access to food formulas against the Ministry of Health in Brazil in 2013. Methods: Exploratory and descriptive study of lawsuits against the Ministry of Health in 2013. Descriptors included: gender, age and disease of those who requested formulas, region of origin, food formulas, legal representation, diagnostic confirmation and origin of prescription of food formulas. Results: Between 2007 and 2013, there was a growing number of lawsuits over industrialized nutritional formulas forwarded to the Ministry of Health. The analysis of 168 lawsuits filed in 2013, helped to identify the profile of complainants. Their ages range was below  two years old and above 41 years old; 53% of them were male, and had mainly neurological diseases (39.3%) and endocrine, nutritional and metabolic diseases (33.9%). The majority of lawsuits was filed in the South (36.9%). Over half of nutritional formulas were prescribed by public health services (53.9%) and most of the lawsuits were represented Public Defenders (65.6%). There was a small number of cases that had diagnostic confirmation (40.5%), especially when cases of allergies/food intolerance were identified. Conclusion: The analysis of the profile of lawsuits made in the present study raises issues rarely discussed in the area of food and nutrition; moreover, it provides information that may contribute to the organization of nutritional care in the Unified Health System (SUS). DOI: http://dx.doi.org/10.12957/demetra.2014.10504